1987
DOI: 10.1111/j.1469-8137.1987.tb04886.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiration of Leaves of Barley Infected With Powdery Mildew: Increased Engagement of the Alternative Oxidase

Abstract: SUMMARYLeaves of barley cv. Maris Otter, susceptible to powdery mildew, show a large increase in respiration rate when infected with this fungus. About half of the increase is due to increased electron flow through the cytochrome chain and half through the alternative pathway. The alternative pathway shows increased engagement following infection but no increase in capacity. Respiration is not limited either by substrate or supply of inorganic phosphate. While the increase in activity of the cytochrome path ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…3A and SI Appendix). These included genes associated with the alternative pathway and the γ-aminobutyrate shunt, which could allow for enhanced respiration under stress (15,16). Taken together with previous findings, our data suggest that enhanced respiration primarily functions to provide the energy required to meet the elevated metabolic demands imposed by the fungus.…”
Section: Site-specific Up-regulation Of Respiration May Be Required Tosupporting
confidence: 75%
See 1 more Smart Citation
“…3A and SI Appendix). These included genes associated with the alternative pathway and the γ-aminobutyrate shunt, which could allow for enhanced respiration under stress (15,16). Taken together with previous findings, our data suggest that enhanced respiration primarily functions to provide the energy required to meet the elevated metabolic demands imposed by the fungus.…”
Section: Site-specific Up-regulation Of Respiration May Be Required Tosupporting
confidence: 75%
“…Enhanced respiration has been measured in a PM interaction with susceptible barley, with approximately half of this enhanced respiration associated with the alternative pathway (15). In highly resistant cultivars, enhanced respiration was not observed, whereas in moderately resistant cultivars, slightly enhanced respiration was observed but the alternative pathway was not active (15). In our study, genes involved in respiration, including glycolysis, the tricarboxylic acid cycle, and the mitochondrial electron transport chain, exhibited increased expression in response to PM at the infection site ( Fig.…”
Section: Site-specific Up-regulation Of Respiration May Be Required Tomentioning
confidence: 99%
“…Therefore, the increases in AOX transcript levels, AOX protein, and total and cyanide-resistant, SHAM-sensitive respiration in Arabidopsis leaves infected with Pst most likely take place in the vicinity of necrotizing plant cells. Previous reports have shown that the increases in total and cyanide-resistant plant respiration can be stronger in a susceptible plant compared with those in a resistant one (Farrar and Rayns, 1987). Such increases are caused by the localization of the pathogen in the avirulent plant-pathogen combination; consequently, less tissue is affected.…”
Section: Discussionmentioning
confidence: 96%
“…The damage to the electron transport chain and an inhibition of non-cyclic photophosphorylation are also the major cause of reduction in chlorophyll concentration and in turn the photosynthetic activity after powdery mildew infestation (Magyarosy et al, 1976;Sharkey, 1985;Scholes and Farrar, 1986). It has been suggested that an increase in host and/or fungal respiration is partially responsible for the reductions in chlorophyll concentrations and photosynthesis in powdery mildew infected tissue (Farrar and Rayns, 1987). Stomata, the opening in the epidermis affect adaptation skills of plants by directing respiration, photosynthesis and transpiration (Brownlee, 2001).…”
Section: Resultsmentioning
confidence: 99%